A Solution‐Processed Organometal Halide Perovskite Hole Transport Layer for Highly Efficient Organic Light‐Emitting Diodes. (10th June 2016) - Tian, Yu; Ling, Yichuan; Shu, Yu; Zhou, Chenkun; Besara, Tiglet; Siegrist, Theo; Gao, Hanwei; Ma, Biwu
Abstract : A new type of hole transport layer (HTL) based on organometal halide perovskite for highly efficient organic light‐emitting diodes (OLEDs) is demonstrated. By solution processing of methylammonium lead chloride (CH3 NH3 PbCl3 ) precursors, smooth neat perovskite thin films can be prepared with high transparency and conductivity. A solution‐ processed multilayer OLED with this perovskite HTL outperforms a device with a PEDOT:PSS layer.